Handbook of alternative fuel technologies - Lee, Sunggyu; Speight, James G.; Loyalka, S. K. (CRC Press, 2015)
While strides are being made in the research and development of environmentally acceptable and more sustainable alternative fuels-including efforts to reduce emissions of air pollutants associated with combustion processes from electric power generation and vehicular transportation-fossil fuel resources are limited and may soon be on the verge of depletion in the near future. Measuring the correlation between quality of life, energy consumption, and the efficient utilization of energy, the Handbook of Alternative Fuel Technologies, Second Edition thoroughly exa.
Keywords: Fuel -- Handbooks, manuals, etc.; Fuel switching -- Handbooks, manuals, etc.; Power resources -- Handbooks, manuals, etc.; elektronické knihy; electronic books